Detrusor Pressures Change with Repeat Filling Cystometry in Myelodysplastic Children with Neurogenic Lower Urinary Tract Dysfunction - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Purpose: The International Children's Continence Society recommends urodynamics repeated at least twice for the optimal result. We aimed to search if 3 times repeat filling urodynamics in the same session would change the urodynamics parameters in children with neurogenic lower urinary tract dysfunction due to myelodysplasia. Materials and Methods: We investigated urodynamic reports and charts of 80 consecutive children with neurogenic lower urinary tract dysfunction due to myelodysplasia who underwent 3 repeat, same session filling cystometry studies between June 2017 and December 2018. Maximum detrusor pressure, maximum cystometric capacity, detrusor leak point pressure, compliance, residual urine volume and maximum cystometric capacity/estimated bladder capacity for age ratio were compared among all 3 filling cystometries. Results: The median age was 4.3 years (IQR 5.8). Of the patients 39 (48.75%) were girls and 41 (51.25%) were boys. Primary pathological finding was myelomeningocele in 69 patients (86.3%). Maximum cystometric capacity, compliance, residual urine and maximum cystometric capacity/estimated bladder capacity for age were found comparable in 3 repeat cystometries. However, maximum detrusor pressure at first filling was higher compared to others (second, p=0.015, and third, p=0.002). Detrusor leak point pressure at the first filling was also higher compared to the third (p<0.001). Detrusor overactivity was persistent in all 3 fillings in 85% of patients (68 of 80). Of the patients 68 (85%) remained in the same risk group according to detrusor leak point pressure (cutoff 40 cmH(2)O). Conclusions: Maximum cystometric capacity and detrusor overactivity are comparable in 3 repeat cystometries but detrusor pressures significantly decrease in the repeat fillings. In our practice we plan our management according to the most worrisome urodynamics parameters for a safer proactive approach.
Keywords: urodynamics; neural tube defects; urinary bladder; neurogenic; urinary bladder; overactive; STANDARDIZATION; BLADDER